2016
DOI: 10.1021/acs.chemmater.6b02522
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Coverage Dependent Reaction Mechanisms of the Copper Atomic Layer Deposition from Copper Dimethylamino-2-propoxide and Diethylzinc

Abstract: Original citationMaimaiti, Yasheng; Elliott, Simon D. (2016) Just Accepted "Just Accepted" manuscripts have been peer-reviewed and accepted for publication. They are posted online prior to technical editing, formatting for publication and author proofing. The American Chemical Society provides "Just Accepted" as a free service to the research community to expedite the dissemination of scientific material as soon as possible after acceptance. "Just Accepted" manuscripts appear in full in PDF format accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
(150 reference statements)
1
15
0
Order By: Relevance
“…In order to determine the step-by-step mechanism and possible side-reactions, we carried out DFT calculations, both a wide screening of many ligands and their intermediates, 37 and a detailed consideration of the kinetics of surface reactions 38 at various coverages. 39 We were particularly interested in finding out how the identity of ligand X affects the process, which species saturate the surface, and why co-deposition of Zn is observed to take place.…”
Section: B Ligand From Organometallic Co-reagent As the Reducing Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine the step-by-step mechanism and possible side-reactions, we carried out DFT calculations, both a wide screening of many ligands and their intermediates, 37 and a detailed consideration of the kinetics of surface reactions 38 at various coverages. 39 We were particularly interested in finding out how the identity of ligand X affects the process, which species saturate the surface, and why co-deposition of Zn is observed to take place.…”
Section: B Ligand From Organometallic Co-reagent As the Reducing Agentmentioning
confidence: 99%
“…The reaction is therefore limited by the coverage of Et groups at the end of step 2b, which we have estimated 39 at four Et groups per (6 × 6) simulation cell, meaning 2 Cu atoms are deposited per cell. Further adsorption of Cu(dmap) 2 is possible in step 1b (for reduction to Cu 0 in step 2a), limited by the availability of sufficiently large segments of bare Cu.…”
Section: B Ligand From Organometallic Co-reagent As the Reducing Agentmentioning
confidence: 99%
“…It was also observed that the growth rate slowed down after reaching a full coverage of the substrate. Cu(dmap) 2 has been employed as a precursor also in other ALD processes of copper metal [ 21–22 ] as well as of copper(I) oxide, [ 23 ] copper(II) oxide, [ 24 ] and hybrid copper‐organic material. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
“…This can in principle be overcome by using more accurate methods [41][42] rather than DFT. However, owing to the complicated reaction pathways that may result from densification 19 or cooperative effects 27,[43][44] , considering large cells with many atoms (e.g., here, 300 atoms with more than 1500 valence electrons) is necessary. This is too computationally demanding for the more accurate methods.…”
Section: Computational Detailsmentioning
confidence: 99%